Journey in blue : A peek into the workers' party of Singapore - Jong, Yee Jenn (World Scientific Publishing Company, 2020)
This book offers a personal and revealing account of Singapore's opposition politics through the eyes of a former Non-Constituency Member of Parliament from the Workers' Party, detailing election campaigns, parliamentary work and reflections on Singapore's political transition.